INTEGRATION OF IT SYSTEMS IN HOSPITAL MANAGEMENT FOR EFFICIENT OPERATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The integration of Information Technology (IT) systems in hospital management plays a vital role in improving operational efficiency, patient care, and administrative workflows. This study explores how various IT solutions—such as Electronic Health Records (EHR), Hospital Information Systems (HIS), and automated billing-streamline processes, reduce errors, and enhance communication among medical staff. By analyzing case studies and current implementations, the research highlights the benefits of IT integration, including improved data accessibility, faster decision-making, and cost savings. Challenges such as system interoperability, data security, and staff training are also discussed. Ultimately, the effective integration of IT systems is essential for modern hospitals aiming to deliver high-quality healthcare services while optimizing resource use.